Benefits Of Learning Based On Information And Communication Technology Media - Hartarto, Wilen; Meriyati, Meriyati; Hijriyah, Umi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Teachers already have competencies, namely pedagogic competence, personality competence, social competence, professional competence, and leadership competence. and leadership competence, but in implementing this needs to be improved again to be more optimal, especially in terms of effective use of information technology-based learning in the learning process learning. Based on the above, this research needs to be done to describe the utilization of Information and Communication TechnologyBased Learning Media in Islamic Education Learning. Information and Communication TechnologyBased Learning Media in Islamic Religious Education Learning at SMK Bina Mulya Bandar Lampung, Indonesia. This research seeks to analyze how the actual picture of the utilization of learning media based on communication and communication technology (ICT) in The subjects in this research were, 1 ICT teacher; 4 teachers of non-educational subjects; 2 of them were Islamic Education teachers; and 2 of them were Islamic Education teachers. Two of them are PAI teachers, and the other 20 are students at SMK Bina Mulya Bandar Lampung. 20 students were at the school. Data were collected by observation, interview, and documentation methods. Data analysis was carried out using Miles and Huberman techniques. then to examine the validity of the data, researchers used triangulation.